Hubungan Penurunan Fungsi Kognitif dengan Stroke Iskemik di RSUD Mangusada - Anak Agung Ngurah Agung Bayu Sutha; Saktivi Harkitasari; Dewa Ayu Agung Alit Suka Astini (Aesculapius Medical Journal, 2023)
Stroke is a neurological disorder that attacks central nervous system. Around 80-90% stroke patients suffer from ischemic stroke. Ischemic stroke is known to have higher potential of causing its sufferer disability. The decline of cognitive function is a condition that is caused by ischemic stroke. If someone experiences decline of cognitive function, it is hard for the person to live independently, reduces productivity, and lowers quality of life. The purpose of this research was to examine the correlation between the cognitive decline and ischemic stroke at Mangusada Regional General Hospital, Badung. This research was an analytical-observational study with cross-sectional design. The research subject sampling technique was consecutive sampling. The research subjects comprised of 70 people with 1:1 ratio, they are 35 ischemic stroke patients and 35 non-ischemic stroke patients who visited the neuro polyclinic at Mangusada Regional General Hospital in December 2021 until February 2022. The data sampling was performed using MoCA-Ina questionnaire. The data were processed and analyzed using contingency coefficient correlation test. The test obtained p value = 0,001 which implied 95% confidence level, it showed that there was significant correlation, and the correlation level is categorized low because the correlation coefficient was 0,378. The conclusion of this research is that there is significant correlation, and the correlation level is categorized low between the cognitive decline and ischemic stroke at Mangusada Regional General Hospital.